ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NET PROFIT MARGIN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Heri Kurniansyah (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2018)
This study analyzes the effect Current Ratio, Working Capital Turnover and Debt Ratio of toNet Profit Margin . Secondary data were obtained from annual report period 2013-2017. This study usedsampel of 10 manufacture company especially pharmacy sub sector taken by Purposive Sampling.Multiple linear regression analysis isused to explain the effect of explanatory several variable todependent variable. The study found that has no sgnificant effect Current Ratio and Debt Ratio on NetProfit Margin. Meanwhile, Working Capital Turnover is positively related to Net Profit Margin.This studyfound that 11,4% Net Profit Margin influenced by Current Ratio, Working Capital Turnover and DebtRatio while the side of 88,6% influenced by another factor.